Decision Support System and Performance Evaluation of the Digesting System of a Paper Plant - Khanduja, Rajiv; Tewari, P. C.; Chauhan, R. S. (Prabandhan: Indian Journal of Management, 2009)
The present paper deals with the decision support system and performance evaluation of the Digesting system of a paper plant. The paper plant is a complex and repairable engineering unit, which comprises of various systems including chipping, digesting, washing, bleaching, screening, stock preparation and paper making etc. One of the most important functionaries of a paper plant is Digesting system where the wooden chips from the storage silos through the belt conveyor are fed to digester (a large pressure-cooking vessel), the steam is forced from the bottom in the digester. The lignin and other fibers present in the wooden chips get dissolved. Then the cooked chips are passed through various systems like washing, bleaching, screening and paper making etc. to convert into the paper. The Digesting system of a paper plant consists of four subsystems arranged in series and parallel configurations. The decision support system for Digesting system has been designed with the help of mathematical formulation based on Markov Birth-Death process. Using probabilistic approach, the differential equations have been developed. Then these equations are further solved by using normalizing conditions so as to determine the steady state availability i.e. measure of performance of the Digesting system of a paper plant. So the performance of each subsystem of the Digesting system of a paper plant also has been analyzed. The objective of decision support system developed is to decide about the relative maintenance priorities for four subsystems of the Digesting system. Therefore, the findings of this paper will be highly useful to the plant management for timely execution of best possible maintenance strategies and hence to enhance the system performance.